Calcium carbonate and sulfate of possible extraterrestrial origin in the EETA 79001 meteorite - Gooding, James L.; Zolensky, Michael E.; Wentworth, Susan J. (1988)
Two varieties of Ca-carbonate were found in a total of three interior (greater than 2-cm depth) samples of glass inclusions from the shergottite meteorite, Elephant Moraine, Antarctica, A79001. Two of the samples, including the largest deposit around a vug near the center of the meteorite (8-cm depth), contained veins of granular calcite with significant Mg and P, either as Mg-calcite with dissolved P or as calcite with very finely intergrown Mg-bearing phosphate. The second variety, which occurred in a third sample with a previously documented high concentration of trapped gases, consisted of disseminated 10-20-micron anhedral grains of nearly pure CaCO3 and was intimately associated with laths and needles of Ca-sulfate (possibly gypsum). All evidence considered, it is probable that both varieties of Ca-carbonate (and the Ca-sulfate) formed on a planetary body (probably Mars) before the meteorite fell on earth.